Socio-economic status and risk of tuberculosis: a case-control study of HIV-infected patients in Asia - Jiamsakul, Awachana; Lee, Man Po; Nguyen, Kinh Van; Merati, Tuti Parwati; Cuong, Do Duy; Ditangco, Rossana; Yunihastuti, Evy; Ponnampalavanar, Sasheela; Zhang, Fujie; Kiertiburanakul, Sasisopin; Avihingasanon, Anchalee; Ng, Oon Tek; et al. (International Union Against Tuberculosis and Lung Disease, 2018)
SETTING: Tuberculosis (TB) is the most common human immunodeficiency virus (HIV) related opportunistic infection and cause of acquired immune-deficiency syndrome related death. TB often affects those from a low socio-economic background. OBJECTIVE : To assess the socio-economic determinants of TB in HIV-infected patients in Asia. DESIGN: This was a matched case-control study. HIVpositive, TB-positive cases were matched to HIVpositive, TB-negative controls according to age, sex and CD4 cell count. A socio-economic questionnaire comprising 23 questions, including education level, employment, housing and substance use, was distributed. Socio-economic risk factors for TB were analysed using conditional logistic regression analysis. RESULT S : A total of 340 patients (170 matched pairs) were recruited, with 262 (77.1%) matched for all three criteria. Pulmonary TB was the predominant type (n = 115, 67.6%). The main risk factor for TB was not having a university level education (OR 4.45, 95%CI 1.50-13.17, P=0.007). Burning wood or coal regularly inside the house and living in the same place of origin were weakly associated with TB diagnosis. CONCLUS IONS : These data suggest that lower socioeconomic status is associated with an increased risk of TB in Asia. Integrating clinical and socio-economic factors into HIV treatment may help in the prevention of opportunistic infections and disease progression.